2018
DOI: 10.1136/neurintsurg-2018-013776
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylcholine surface modified flow diverter associated with reduced intimal hyperplasia

Abstract: OCT is a promising technique for immediate and long-term evaluation of flow diverter stent treatments. In an animal model, phosphorylcholine surface modified flow diverters induces less NIH after stent implant without reducing aneurysm occlusion rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 29 publications
1
17
1
Order By: Relevance
“…This finding suggests that PC surface modification results in similar rates of in-stent stenosis or late loss between PED Flex and Shield. However, Caroff et al reported that a surface-modified flow diverter had significantly less in-stent neointimal hyperplasia in a rabbit model 20. The difference in animal model might cause the difference between their result and ours.…”
Section: Discussioncontrasting
confidence: 60%
“…This finding suggests that PC surface modification results in similar rates of in-stent stenosis or late loss between PED Flex and Shield. However, Caroff et al reported that a surface-modified flow diverter had significantly less in-stent neointimal hyperplasia in a rabbit model 20. The difference in animal model might cause the difference between their result and ours.…”
Section: Discussioncontrasting
confidence: 60%
“…11 The authors concluded that, in comparison with Pipeline Flex, Pipeline Shield results in earlier neointimal formation, resulting in reduced thrombosis, reduced late neointimal hyperplasia, and a reduced in-stent stenosis rate. Furthermore, a recent preclinical study has demonstrated reduced intimal hyperplasia without reducing aneurysm occlusion rates by using the Shield technology 17…”
Section: Discussionmentioning
confidence: 99%
“… 4 The PED Shield induces less neointimal hyperplasia in rabbit models at 30 days compared with the PED Classic (5.7% vs 8.9%; p<0.0001) based on OCT and histopathological findings (r 2 =0.83; p<0.0001). 10 The superior MCA branch in our patient was jailed and despite concerns for vessel occlusion, previous in vivo studies have demonstrated branches to remain patent despite a high surface tissue coverage 11 ; therefore, treating the patient with PED Shield suggests an added benefit in this patient’s case. …”
Section: Discussionmentioning
confidence: 61%